FRAUD OF FINANCIAL STATEMENTS IN DIAMOND THEORY'S PERSPECTIVE: EMPIRICAL STUDY OF TRANSPORTATION SUB SECTOR COMPANIES IN THE INDONESIA STOCK EXCHANGE - Siregar, Amelia Oktrivina; Prayoga, M. Adam; Sudarmaji, Eka (Fakultas Pendidikan Ekonomi dan Bisnis, 2019)
This study aims to obtain empirical evidence in detecting fraudulent financial statements from the perspective of Â 'fraud diamond theory'. The proxy variables used in this study are the influence of pressure, opportunity, rationalization, and ability. This study uses a sample of transportation sub-sector companies listed on the Indonesia Stock Exchange (IDX) in the period of 2015-2017. This research is expected to contribute to the development of accounting science, especially in the field of forensic accounting regarding factors that can affect companies to conduct fraudulent financial statements by implementing indicators of diamond fraud. Hypothesis testing used multiple linear regression analysis with the help of application eviews software, to help process research data in the form of panel data. The results of this study indicate that pressure, opportunity, rationalization, and ability together were not significantly influence the tendency of fraudulent financial statements.